Plínio Marcos: do texto à tela - Almeida, Alcione Gomes de (2024)
This paper introduces the renowned author Plínio Marcos focusing on themes of interest such as culture, performance, and cultural performances. The introduction aims to provide a concise yet consistent approach to his life and career, thus discussing his influence on Brazilian culture over the decades and nowadays. The discussion initially considers the temporal framework, and remarks emerge regarding the analysis’ corpus. Plínio's theatrical success attracted filmmakers, leading to adaptations of his plays, short stories, and scripts into movies, including Navalha na carne (1970, 1997), Dois perdidos numa noite suja (1971, 2003), Nenê Bandalho (1971), A rainha diaba (1974), Barra pesada (1977), Barrela: escola de crimes (1994), Querô (2006). The primary purpose of this paper is to systematically analyze the cinematographic corpus in chronological order, prioritizing the adaptations of Plínio’s theatrical plays due to their role in the dramatist’s career. This approach facilitates the equilibrium of this extensive work. When it comes to the Plinian universe, it is essential to observe the social role a character plays; their origins; the relationships built; the dialogues’ linguistic selection; the environment where the plot evolves; the progress of the conflict. Accordingly, there are differences between the films and the original text - suppression, complementation, and update, with the Brazilian society and its period characteristics during filming as a horizon, in addition to the Brazilian film industry, which impacts the production, promotion, and reception. A case in point is the CivilMilitary Dictatorship (1964-1985), which, among other authoritarian policies, implemented violent restrictions on society, the Arts, artists, and other professionals in the field. The results of this investigation corroborate with other authors: the singularity, relevance, and power of Plínio Marcos in Brazilian culture in any period. The Santista author strongly opposed the suppression of the Arts and freedom of speech during the Military regime. He was at risk for isolation and became a prominent resistance figure even after political liberalization, without ever soothing his ideas and dissenting voice. His legacy’s endurance and relevance for contemporary society is a consensus. The theoretical base of Mikhail Bakhtin (1988, 2010, 2011, 2014, 2019, 2020) is essential for the effective development of film analysis, considering the ideas provide density for the adaptation’s study and, therefore, viable possibilities to observe and comprehend cinematographic language. When applying the Bakhtinian repertoire to the films, several concepts are valuable to filmmaking characteristics, the stance of the creators, researchers, and the public, as well as the themes explored, expanding beyond an analytical and critical examination. Thus, the analysis of the corpus is primarily supported by: otherness; the self/other; responsible act; non-alibi; the ethical and the aesthetic; the world of theory; the world of culture; dialogism; responsive understanding; discourse genres; theoreticism (critique of the objectification of historicity that constitutes life); refraction; polyphony; ideology; chronotope (involves spatial and temporal relations, originates from the Greek words crónos, meaning time, and tópos, meaning space).